THE APPLICATION OF THE WASPAS METHOD WITH THE SWARA WEIGHTING METHOD APPROACH IN THE SELECTION OF SINGLE COLLEGE MONEY AID BUDIDARMA UNIVERSITY - Murdani; Lince Tomoria Sianturi (INFOKUM, 2021)
Decision making is very necessary in choosing the application for Single Tuition Assistance at Budidarma University because to get Single Tuition assistance is very limited, a selection is carried out before the data is sent to Tertiary Education Institutions I North Sumatra. Solving the problem above requires a way to make a decision on the Selection of Single Tuition Aid at Budidarma University with the WASPAS method. The reason for using the WASPAS method for making a decision can help and make it easier to do the selection. The weighting approach using the SWARA method, with a decision-making method so that the results help decision makers make decisions accurately. Keywords: Decision, Selection, Single Tuition Assistance, Waspas Method and Swara method